CONFLICT MANAGEMENT FROM A PRACTITIONER PERSPECTIVE: SEBUAH STRATEGI MEMPERSIAPAKAN ORGANISASI UNTUK TERLIBAT DALAM KONFLIK KONSTRUKTIF - Janna, Niftahul; Julaiha, Siti; Sudadi, Sudadi (Jurnal Manajemen Pendidikan, 2024)
Conflict is an inevitability inherent in human life. Conflict within organizations cannot be eradicated as it is a logical consequence of individual interactions that result in disputes or gaps between expectations and reality. Knowledge about conflict management and strategies for preparing organizations to engage in constructive conflict is essential. This study is qualitative research utilizing a literature review. The results of this study indicate that the initial step in preparing an organization to engage in constructive conflict is to build trust through discussions on hypothetical cases and formulating possible scenarios, developing dialogue and mediation skills by training specific communication skills, and enhancing understanding of general behaviors that may arise as responses during conflict. The next steps involve deepening the commitment to diversity and social justice by being open to others' perspectives, acknowledging the uniqueness of others' views and understandings, considering internal and external factors that may influence others' views and attitudes, repeating and summarizing what has been communicated by others, considering expressions and hidden messages in communication, setting clear boundaries, determining basic discussion rules.